1990
DOI: 10.1144/gsl.sp.1990.055.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Timing, style and sedimentary evolution of Late Palaeozoic-Mesozoic extensional basins of East Greenland

Abstract: The late Palaeozoic-Mesozoic sedimentary basins of East Greenland record a complex series of events which eventually led to the successful opening of the Norwegian-Greenland Sea in the late Palaeocene. Major tectonic events and regional sea-level changes caused by plate movements and reorganizations, overprinted by the effects of local tectonics and associated sea-level changes are reflected in thick, unconformity bounded sequences. Caledonian crustal shortening and thickening culminated in the Silurian, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
221
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(229 citation statements)
references
References 40 publications
8
221
0
Order By: Relevance
“…Terrace were deposited in the same seaway as age equivalent strata on East Greenland (Surlyk, 1990;Alsgaard et al, 2003;Vosgerau et al, 2004;Eide et al, 2016). Relatively short source catchments in the Baltic Shield were present east of the Halten Terrace during the Cretaceous (Martinsen et al, 2005;Elliott et al, 2012;Elliott et al, 2015;, and it has been M A N U S C R I P T…”
Section: Catchment and Hinterlandmentioning
confidence: 99%
“…Terrace were deposited in the same seaway as age equivalent strata on East Greenland (Surlyk, 1990;Alsgaard et al, 2003;Vosgerau et al, 2004;Eide et al, 2016). Relatively short source catchments in the Baltic Shield were present east of the Halten Terrace during the Cretaceous (Martinsen et al, 2005;Elliott et al, 2012;Elliott et al, 2015;, and it has been M A N U S C R I P T…”
Section: Catchment and Hinterlandmentioning
confidence: 99%
“…Larsen & Marcussen (1992) suggested that the basin infill there might even be up to 18 km thick. Following the postCaledonian extension with fault-controlled Devonian basins, late Jurassic -early Cretaceous rifting resulted in the deposition of marine sediments over the Devonian sediments in Jameson Land (Surlyk 1990). …”
Section: Ne Greenland Continental Marginmentioning
confidence: 99%
“…Permian and Triassic broadly E-W-directed extension between Eurasia and Greenland resulted in the formation of numerous large half-graben basins widely distributed at the margins (Ziegler, 1989;Brekke et al 1999;DorĂŠ et al 1999;Surlyk, 1990). Jurassic E-W extension between Eurasia and North America-Greenland gave way to a dominantly NW-SE-directed extension in Early to Middle Cretaceous times (DorĂŠ et al 1999).…”
Section: A Tectonic Settingsmentioning
confidence: 99%